2020
DOI: 10.1002/uog.20388
|View full text |Cite
|
Sign up to set email alerts
|

Core outcome set for studies investigating management of selective fetal growth restriction in twins

Abstract: Objective Selective fetal growth restriction (sFGR) occurs in monochorionic twin pregnancies when unequal placental sharing leads to restriction in the growth of just one twin. Management options include laser separation of the fetal circulations, selective reduction or expectant management, but what constitutes the best treatment is not yet known. New trials in this area are urgently needed but, in this rare and complex group, maximizing the relevance and utility of clinical research design and outputs is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…43 It is intended that these consensus outcome measures will be used for core outcomes included in other core outcome sets relevant to the health of women and newborn infants. [44][45][46][47][48][49][50]…”
Section: Discussionmentioning
confidence: 99%
“…43 It is intended that these consensus outcome measures will be used for core outcomes included in other core outcome sets relevant to the health of women and newborn infants. [44][45][46][47][48][49][50]…”
Section: Discussionmentioning
confidence: 99%
“…Our results illustrate the importance of using standard diagnostic criteria of sFGR and could explain the large variation among the published studies. Recent international efforts have also focused on standardizing the outcomes reported in twin studies [24,25]. One future research priority, which has been identified by the global twins and multiples priority setting partnership, is how we can assess the growth of twin infants after birth and how to ensure that they follow a satisfactory growth trajectory [26].…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Similarly, in sFGR 96 different outcomes were found from 36 studies in a systematic review, therefore, the same group felt that it was important to standardise outcome reporting in this condition (CHOOSE-FGR). This was also performed using a stepwise approach inclusive of participants from different multidisciplinary perspectives, as well as patients themselves, leading to a concluding set of 11 core outcomes to aid with future research reporting 129 .…”
Section: Core Outcomes In Twinsmentioning
confidence: 99%